Non-English speakers' perspectives on the utilization of Padlet - Masykuri, Edi Sunjayanto; Alekseevna, Ekaterina Konstina (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
This study sought to ascertain EFL students' perspectives regarding the utilization of Padlet in writing. This investigation was conducted with first-year students. This study involves four students from three classes of an Economy and Social Science Department of a state pedagogical university in Russia. The sampling was conducted purposefully according to the criteria established by the researchers. The study uses qualitative descriptive and employed case study methodologies. Data gathering was conducted through interviews. The findings indicated three student affective perspectives about the use of Padlet in writing: 1). Utility: students are able to compose phrases in English on Padlet, while others are unable to do so. 2) Usability: Students see writing tasks in English on Padlet as straightforward. 3) Accessibility: Students believe the learning process on Padlet is readily accessible, while some find it challenging to navigate. The inquiry into this study's outcomes revealed that many students encountered challenges in the online learning process, specifically identifying inadequate internet access and unstable network connectivity as impediments to their effective and timely participation in lessons on Padlet.Keywords: Asynchronous learning, Padlet, Non-English speaker, Student’s perception, Russian students